Study of genetic diversities and relatedness of Iranian citrus genotypes using morphological and molecular markers - Hajar Abedinpour; Nad Ali Babaeian Jelodar; Gholam Ali Ranjbar; Behrouz Golein (Journal of Plant Molecular Breeding, 2015)
Having knowledge about genetic relationships among accessions is necessary for developing breeding strategies to produce improved cultivars. In present study, genetic diversity and inter-relationship among 29 genotypes of citrus were comparatively analyzed using morphological and RAPD markers. Significant variability was observed among citrus genotypes for 61 quantitative and qualitative morphological characters of leaves, fruits and seeds. Furthermore, the RAPD markers revealed a high polymorphism rate (91.82 %). A pair-wise similarity value between genotypes ranged from 0.14 to 0.97 with average of 0.62. Both morphological and molecular analysis indicated a high degree of variation among studied genotypes. In current research, genotypes “pummelo” and “mandarin” were confirmed as true species of citrus in distinct cluster. Results of present study proved that both of morphological and molecular markers are potential tools for determining genetic diversities and genetic relationships of citrus genotypes and can be used in citrus breeding programs.